Determining suitable meteorological drought and vegetation indices for monitoring drought and crop yield in Srepok River basin, Vietnam - Luc, Huynh Cong; Van Viet, Luong; Hung, Bui Dang (Agriculture and Natural Resources, 2025)
Importance of the work: Drought is a severe natural disaster that damages crop yields. Objectives: To identify suitable meteorological drought and vegetation indices for monitoring drought and crop yield in the Srepok basin, Vietnam. Materials and Methods: The study used the standardized precipitation index (SPI), effective drought index (EDI), vegetation health index (VHI), vegetation condition index (VCI), temperature condition index (TCI) and crop yields from 2000 to 2022. Simple and multiple correlation coefficients between these indices and crop yields were analyzed. Results: SPI had a better relationship with the vegetation indices and crop yields than EDI. VHI, TCI and VCI, in descending order, had good relationships with meteorological drought indices. The pairing of VHI and the SPI at a 6-month time scale (SPI6) was the most suitable for monitoring drought in the study area during the dry season (February to early May). The best choice for crop yields was the SPI at a 5-month time scale (SPI5), taken at 9 mth and 3 mth before harvest for warning of the impact of drought on coffee and winter-spring rice, respectively. Main finding: In the Srepok River basin, the SPI6-VHI combination was most effective for drought monitoring during February–May, while SPI5 with different lead times (9 mth for coffee and 3 mth for rice) provided optimal yield forecasting.